VARIASI FONOLOGIS BAHASA MADURA YANG DIGUNAKAN MASYARAKAT KELURAHAN SIANTAN HULU DI KECAMATAN PONTIANAK UTARA - Mufidah, Riatul; Amriani Amir, M.Hum, Amriani Amir, M.Hum; Mellisa Jupitasari, M.Pd, Mellisa Jupitasari, M.Pd (Universitas Tanjungpura, 2024)
This research will be carried out in Siantan Hulu Village, North Pontianak District, considering that the majority of the population is Madurese who regularly communicate in Madurese with various dialects. This research aims to describe the phonological variety, namely variations of vocoids and contoids in Madurese as well as the application of Indonesian language learning according to the phonological variety of spoken Madurese in Siantan Hulu District, North Pontianak. Area A descriptive approach was used in this research, along with a qualitative form of research. Siantan Hulu Village District provided data for this research. The approach used in this research is interviews, namely taking notes, observing, taking notes and noting used to collect data in this research. Observational persistence is the approach used in this research to verify the credibility of the data. The phonological diversity of the Madurese language in Siantan Hulu Regency was studied and 25 variants were found, including 9 vocoid (vowel) variations and 16 contoid (consonant) variations. This research was carried out in the context of descriptive text so that it was presented at the vocational school level